Pengaruh Citra Destinasi Dan Kepuasan Wisatawan Terhadap Revisit Intention Di Kota Padang: (Studi Kasus Daya Tarik Wisata Pantai Padang) - Meshy Mulyani; Feri Ferdian (Universitas Katolik Widya Karya Malang, 2023)
This research is based on phenomena related to destination image, tourist satisfaction, and revisit intention at Padang Beach Tourism Attraction. This research applies a quantitative approach with a causal-associative method. The sample consisted of 100 tourists selected through purposive sampling. Data were collected through the use of questionnaires that have been validated and tested for reliability. The data were processed through multiple linear regression analysis using SPSS version 26.00. The results showed that destination image and tourist satisfaction play a positive and significant role in the intention to return to visit Padang Beach Tourism Attraction. The results state that destination image and tourist satisfaction together contribute significantly (around 20%) to the intention to return to visit Padang Beach.